THE EFFECTIVENESS OF GALENIC CREAM OF DURIAN PEEL EXTRACT AND CHITOSAN FOR TREATMENT OF DIABETIC ULCERS - Agustin, Wahyu Rima; Harti, Agnes Sri; Crisdian S, Hanugrah Ardya; Saputro, Sutiyo Dani; Saelan, Saelan (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Introduction: The chemical substance of durian peel (Durio zibethinus L.) is a polysaccharide polymer of D-galacturonic acid which is polar and anti-microbial. Chitosan is a derivative of chitin from the peels of Crustaceae animals, which is polycationic and antimicrobial; biodegradable, and biocompatible wit animal tissues. Diabetic ulcers are chronic wounds due to neurological disorders and vascular disorder in the legs, causing tissue damage. The purpose of the study was to analyze the effectiveness of galeni preparations of durian peel extract and chitosan for the treatment of diabetic ulcers.Method: This research is experimental including testing the quality of 5% durian peel extract cream preparations; 2% chitosan, a mixture of both ratio = 1:1; 1:2 physically, chemically, and microbiologically,and the rate of wound healing in test animals. Statistical data analysis of One Way Anova parametric test.Results: The results showed that the preparation of galenic durian peel extract cream and chitosan and their combination ratio (1:1), (1:2) could be formulated and met the quality test of cream preparations physically, chemically, and microbiologically according to the requirements of BPOM No. 32 of 2019 and is effective for healing diabetic ulcers on the 8th day.Conclusions: The preparation of galenic durian peel extract cream and chitosan and their combination ratio (1:1), (1:2) can potentially be developed as a cream preparation for healing diabetic ulcers.